Are Tax Amnesties Good for Us All? Understanding Influence of Tax Amnesties on Benefiters and Non-Benefiters - SARISOY, İDRİS (OXFORD UNIV PRESS, 2020)
This article aims to investigate the effect of tax amnesties on tax compliance decisions of taxpayers. In particular, we focused on Turkish taxpayers' fairness perceptions and their voluntary tax compliance after the recent legislation of 6736, which is claimed to be the biggest tax amnesty (for example, tax debt restructuring legislation) in the last decade. This article also investigates the difference between tax amnesty benefiters and non-benefiters when it comes to their tax compliance and fairness perceptions. This article starts with a summary of the literature with a particular focus on Turkey. The research looks into the influence of the perception of tax amnesties on fairness and tax compliance of taxpayers while controlling for widely discussed factors that influence tax compliance such as risk awareness and government trust. The survey was conducted with 1028 participants and a structural model was constructed to test for the above-mentioned effects. We found fairness perception of the taxpayers is negatively affected by tax amnesties. Additionally, the findings showed that acceptance/approval of taxpayers on tax amnesty practice is effective on taxpayer compliance. Finally, only tax amnesty benefiters' fairness perception is negatively influenced by tax amnesties while the effect is not significant on benefiters.
Keywords: tax amnesties; fairness perception; risk perception; government trust; tax compliance; FAIRNESS; JUSTICE; TAXPAYERS; MORALE; NORMS